2015
DOI: 10.1371/journal.pone.0139330
|View full text |Cite|
|
Sign up to set email alerts
|

Endocytosed β2-Microglobulin Amyloid Fibrils Induce Necrosis and Apoptosis of Rabbit Synovial Fibroblasts by Disrupting Endosomal/Lysosomal Membranes: A Novel Mechanism on the Cytotoxicity of Amyloid Fibrils

Abstract: Dialysis-related amyloidosis is a major complication in long-term hemodialysis patients. In dialysis-related amyloidosis, β2-microglobulin (β2-m) amyloid fibrils deposit in the osteoarticular tissue, leading to carpal tunnel syndrome and destructive arthropathy with cystic bone lesions, but the mechanism by which these amyloid fibrils destruct bone and joint tissue is not fully understood. In this study, we assessed the cytotoxic effect of β2-m amyloid fibrils on the cultured rabbit synovial fibroblasts. Under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 53 publications
2
27
0
Order By: Relevance
“…We assessed the effect of β2‐m amyloid fibrils on the cultured synovial fibroblasts derived from rabbit periarticular soft tissue (HIG‐82 cells) . We found that endocytosed amyloid fibrils cause both necrosis (plasma membrane disruption) and apoptosis of the cells by disrupting endosomal/lysosomal membranes with the leakage of the fibrils into the cytosol and adjacent to mitochondria (Fig.…”
Section: The Cytotoxic Mechanisms Of β2‐m and Other Amyloid Fibrilsmentioning
confidence: 99%
“…We assessed the effect of β2‐m amyloid fibrils on the cultured synovial fibroblasts derived from rabbit periarticular soft tissue (HIG‐82 cells) . We found that endocytosed amyloid fibrils cause both necrosis (plasma membrane disruption) and apoptosis of the cells by disrupting endosomal/lysosomal membranes with the leakage of the fibrils into the cytosol and adjacent to mitochondria (Fig.…”
Section: The Cytotoxic Mechanisms Of β2‐m and Other Amyloid Fibrilsmentioning
confidence: 99%
“…Thus, our results suggest that apoA-I Iowa fibrils may be internalized by cells and transported to lysosomes in a dynamin- and actin dynamics-dependent, but caveolin-independent, manner. Similarly, dynasore and cytochalasin D reportedly reduced the cytotoxicity of β 2 -microglobulin amyloid fibrils, possibly by inhibiting fibril internalization 18 57 . Nonphagocytic cells internalized beads having a diameter of 5.5 μM in a clathrin- and dynamin-dependent fashion 58 .…”
Section: Discussionmentioning
confidence: 96%
“…Pinocytosis-dependent and dynamin-dependent endocytoses were implicated in the internalization and cytotoxicity of β 2 -microglobulin amyloid fibrils 18 57 . In the present study, cytochalasin D and dynasore inhibited degradation of apoA-I Iowa fibrils, whereas nystatin did not.…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that the phagocytosis of AApoAII amyloid fibrils by monocytes/macrophages contributed to the transmission of amyloidosis when the cells were transfused to recipients. Tissue cells could be damaged by endocytosis of amyloid fibrils in various amyloidoses [ 22 , 35 ]. Also, Aβ was demonstrated to bind to RBCs [ 23 ].…”
Section: Discussionmentioning
confidence: 99%